2014
DOI: 10.1016/j.jebo.2014.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Friends do let friends buy stocks actively

Abstract: This research is the fi rst to provide empirical evidence that social interaction is more prevalent amongst active rather than passive investors. While previous empirical work, spearheaded by Hong, Kubik, and Stein (2004), shows that proxies for sociability are related to participation in asset markets, the literature is unable to distinguish between the types of participants because of data limitations. I address this shortcoming by using data from the Consumer Expenditure Quarterly Interview Survey on indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Survey evidence indicates that greater household involvement in social activities is associated with greater stock market participation both in the U.S. (Hong, Kubik, and Stein 2004) and in ten European countries (Georgarakos and Pasini 2011). Furthermore, Heimer (2014) documents that social interaction is more prevalent amongst active investors who buy and/or sell stocks than passive investors who hold U.S. savings bonds, thereby supporting our explanation for the active investing puzzle in which informal communication tends to promote active rather than passive strategies.…”
Section: Investor Behavior In a Social Networksupporting
confidence: 60%
“…Survey evidence indicates that greater household involvement in social activities is associated with greater stock market participation both in the U.S. (Hong, Kubik, and Stein 2004) and in ten European countries (Georgarakos and Pasini 2011). Furthermore, Heimer (2014) documents that social interaction is more prevalent amongst active investors who buy and/or sell stocks than passive investors who hold U.S. savings bonds, thereby supporting our explanation for the active investing puzzle in which informal communication tends to promote active rather than passive strategies.…”
Section: Investor Behavior In a Social Networksupporting
confidence: 60%
“…Since it is beyond the scope of our data to address this critique, we direct readers towards contemporaneous research. Using data from a representative household survey and an approach similar to Hong, Kubik, and Stein (2004), Heimer (2014) shows that social individuals are more likely to exhibit higher portfolio turnover conditional on asset market participation. (Han and Yang (2013), Walden (2013), and Andrei and Cujean (2014)).…”
Section: Discussionmentioning
confidence: 99%
“…Karabulut (2013) found that investors who score high on competence trait tend to seek less information from financial advisors because they may be more willing to bet on their own judgment, rather than to rely on financial advice. Heimer (2014) showed that active investors are more extensively involved in social interaction than passive investors; therefore, informal communication in active investors is more likely to promote investment strategies. Karabulut (2013) also showed that overconfident investors seek less information from financial advisors which is in accordance with Guiso and Jappelli (2006) who suggested that overconfidence investors are less likely to rely on the information obtained from financial advisors; therefore, they collect information directly.…”
Section: Literature Reviewmentioning
confidence: 99%